Analisis Metode Pembelajaran Aktif dan Literasi Digital terhadap Motivasi dan Hasil Belajar Mahasiswa dengan SEM-PLS - Sipayung, Maurits Sahata; Kurniawan, Deddy (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study examines the impact of active learning methods and digital literacy on learning motivation as an intervening variable influencing student learning outcomes in the Enterprise System course. Conducted over five months, it employed flipped learning, blended learning, e-learning, digital quizzes, LMS, audiovisual, and case-study discussions. Data from 31 students was collected via online questionnaires and academic scores. Using SEM-PLS (SmartPLS 4), results show active learning methods and digital literacy significantly enhance learning motivation, which positively influences student learning outcomes. This highlights the importance of integrating digital literacy and active learning for improved learning motivation and academic performance.